Pelaksanaan Upaya Yang Diberikan Untuk Melindungi Anak Dari Ekploitasi Untuk Dijadikan Pengemis - Sunarto, Atika (Universitas Islam Sumatera Utara, 2022)
The cause of the child ng exploited to serve as the perpetrator of a crime is an internal factor. This internal factor is more directed to a family's situation factor which describes a situation within the individual and the family of a child who is exploited to be a beggar who encourages them to beg. These factors are individual and family poverty, age, formal education, parental permission, low skills and mental attitude. Criminal law policy against perpetrators who send children as beggars can be categorized as perpetrators of criminal acts so that the perpetrators may be subject to criminal or imprisonment sanctions or both at once. The threat of imprisonment is a maximum of 10 (ten) years, while a maximum fine of Rp. 200,000,000.00 (two hundred million rupiah). Criminal liability for the perpetrator who commits the child as a beggar is an act as regulated in the provisions of Article 301 of the Criminal Code and Article 76 I and Article 88 of Law Number 35 Year 2014 About Amendment to Law Number 23 Year 2002 on Child Protection regulates the subject of ordering the child begging the begging is a criminal act and to the perpetrator may be subject to criminal sanctions. Keywords: Children, Begging